Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine which ordered pair satisfies both inequalities
[tex]\[ y > -2x + 3 \][/tex]
[tex]\[ y \leq x - 2 \][/tex]
we need to check each given ordered pair step-by-step.
Let's analyze each pair:
1. Pair (0, 0):
[tex]\[ y = 0, x = 0 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ 0 > -2(0) + 3 \implies 0 > 3 \quad \text{(False)} \][/tex]
Since this pair does not satisfy the first inequality, we can move on to the next pair.
2. Pair (0, -1):
[tex]\[ y = -1, x = 0 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ -1 > -2(0) + 3 \implies -1 > 3 \quad \text{(False)} \][/tex]
Since this pair does not satisfy the first inequality, we can move on to the next pair.
3. Pair (1, 1):
[tex]\[ y = 1, x = 1 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ 1 > -2(1) + 3 \implies 1 > 1 \quad \text{(False)} \][/tex]
Since this pair does not satisfy the first inequality, we can move on to the next pair.
4. Pair (3, 0):
[tex]\[ y = 0, x = 3 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ 0 > -2(3) + 3 \implies 0 > -6 + 3 \implies 0 > -3 \quad \text{(True)} \][/tex]
Now, check the second inequality \( y \leq x - 2 \):
[tex]\[ 0 \leq 3 - 2 \implies 0 \leq 1 \quad \text{(True)} \][/tex]
This pair satisfies both inequalities.
Therefore, the ordered pair that makes both inequalities true is:
[tex]\[ (3, 0) \][/tex]
[tex]\[ y > -2x + 3 \][/tex]
[tex]\[ y \leq x - 2 \][/tex]
we need to check each given ordered pair step-by-step.
Let's analyze each pair:
1. Pair (0, 0):
[tex]\[ y = 0, x = 0 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ 0 > -2(0) + 3 \implies 0 > 3 \quad \text{(False)} \][/tex]
Since this pair does not satisfy the first inequality, we can move on to the next pair.
2. Pair (0, -1):
[tex]\[ y = -1, x = 0 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ -1 > -2(0) + 3 \implies -1 > 3 \quad \text{(False)} \][/tex]
Since this pair does not satisfy the first inequality, we can move on to the next pair.
3. Pair (1, 1):
[tex]\[ y = 1, x = 1 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ 1 > -2(1) + 3 \implies 1 > 1 \quad \text{(False)} \][/tex]
Since this pair does not satisfy the first inequality, we can move on to the next pair.
4. Pair (3, 0):
[tex]\[ y = 0, x = 3 \][/tex]
Check the first inequality \( y > -2x + 3 \):
[tex]\[ 0 > -2(3) + 3 \implies 0 > -6 + 3 \implies 0 > -3 \quad \text{(True)} \][/tex]
Now, check the second inequality \( y \leq x - 2 \):
[tex]\[ 0 \leq 3 - 2 \implies 0 \leq 1 \quad \text{(True)} \][/tex]
This pair satisfies both inequalities.
Therefore, the ordered pair that makes both inequalities true is:
[tex]\[ (3, 0) \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.